2015
DOI: 10.3109/09687637.2015.1036006
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and narratives – Drug users with antisocial personality disorder retelling the process of treatment and change

Abstract: Experiences and narratives-Drug users with antisocial personality disorder retelling the process of treatment and change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Study participants were selected from 175 patients who participated in a pragmatic randomised trial (Watkins et al, ; Delgadillo et al, ) to test the efficacy of a brief psychoeducational intervention for ASPD – the Impulsive Lifestyle Counselling program as a supplement to standard substance abuse treatment in an outpatient context (see also Thylstrup et al, , ; Thylstrup & Hesse, ). The trial took place between January 2012 and June 2014 at 13 public outpatient substance abuse treatment services in Denmark.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study participants were selected from 175 patients who participated in a pragmatic randomised trial (Watkins et al, ; Delgadillo et al, ) to test the efficacy of a brief psychoeducational intervention for ASPD – the Impulsive Lifestyle Counselling program as a supplement to standard substance abuse treatment in an outpatient context (see also Thylstrup et al, , ; Thylstrup & Hesse, ). The trial took place between January 2012 and June 2014 at 13 public outpatient substance abuse treatment services in Denmark.…”
Section: Methodsmentioning
confidence: 99%
“…Patients who met inclusion criteria completed baseline assessment, including the OMQ, the Buss–Perry Aggression Questionnaire (BPAQ) and the Addiction Severity Index (ASI) (see subsequent discussions). In the parent study, 175 patients were included, and 192 were excluded; among the latter, 124 did not satisfy criteria for ASPD, and 78 declined to participate (Thylstrup et al, , ). One hundred and twenty‐seven of the trial participants could be included in the present study; 48 were excluded for various reasons (five reported no past year offending behaviour; two did not nominate a most risky offence; and 41 had missing data on one or more of the study questionnaires).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As there were no differences between treatment conditions in the intake, dose titration, drug screening and methadone take-home procedures, there were missed opportunities to test these additional PCC principles. This is particularly relevant, as methadone patients have previously reported dissatisfaction with the comprehensiveness of this treatment [7] and its limited opportunities for shared decision-making [7].…”
Section: Prioritizing the Patient In Patient-centered Addictions Treamentioning
confidence: 99%
“…People in substitution treatment face societal stigmatization and are often highly disciplined by institutions, and these factors may hinder recovery and the development of positive pro-social identities [5,6]. The task for treatment providers will be to develop ways to engage individuals and patient populations in formulating the goals for treatment and specifying what is important to them [7], although this may be difficult [8,9].…”
mentioning
confidence: 99%